DSSBU: A novel mass spectrometry-cleavable analogue of the BS3 cross-linker - Swati, Banerjee; Jakub, Sýs; Aleš, Machara; Petra, Junková; Martin, Hubálek (Journal of proteomics, 2025)
Protein cross-linking has assumed an irreplaceable role in structural proteomics. Recently, significant efforts have been made to develop novel mass spectrometry (MS)-cleavable reagents. At present, only water-insoluble MS-cleavable cross-linkers are commercially available. However, to comprehensively analyse the various chemical and structural motifs making up proteins, it is necessary to target different protein sites with varying degrees of hydrophilicity. Here we introduce the new MS-cleavable cross-linker disulfodisuccinimidyl dibutyric urea (DSSBU), which we have developed in-house for this purpose. DSSBU contains an N-hydroxysulfosuccinimide (sulfo-NHS) reactive group, so it can serve as a water-soluble counterpart to the widely used cross-linker disuccinimidyl dibutyric urea (DSBU). To investigate the applicability of DSSBU, we compared the efficacy of four similar cross-linkers: bis[sulfosuccinimidyl] suberate (BS3), disuccinimidyl suberate (DSS), DSBU and DSSBU with bovine serum albumin. In addition, we compared the efficacy of DSBU and DSSBU with human haemoglobin. Our results demonstrate that the sulfo-NHS group ensures the superior water solubility of DSSBU and thus negates the need for organic solvents such as dimethyl sulfoxide while preserving the effectivity of urea-based MS-cleavable crosslinkers such as DSBU. Additionally, it makes it possible to target polar regions in proteins. The data gathered are available via ProteomeXchange under identifier PXD055284. SIGNIFICANCE: We have synthesized the novel protein cross-linker DSSBU, which combines sulfo-NHS ester chemistry with a mass spectrometry-cleavable urea group. This makes DSSBU a water-soluble, MS-cleavable cross-linker that reacts with amino groups. To our knowledge, it is the first cross-linker which combines all three of these characteristics. We have tested the performance of our novel cross-linker on bovine serum albumin, a model widely used by the cross-linking mass spectrometry community, and on human haemoglobin. We have comprehensively assessed the performance of DSSBU and compared its efficacy with that of three other cross-linkers in current use (BS3, DSS and DSBU). We conclude that our novel cross-linker surpasses its MS-non-cleavable analogue BS3 in performance and that its water solubility eliminates the need for organic solvents while its hydrophilicity allows for the targetting of polar regions in proteins. Therefore, it will likely become a significant addition to the portfolio of N-hydroxysuccinimide ester cross-linkers.
Keywords: Cattle; sukcinimidy; Animals; skot; močovina; lidé; sérový albumin hovězí; Mass spectrometry; proteomika; Serum Albumin, Bovine; Protein conformation; Chemical cross-linking; Cross-Linking Reagents; Water-soluble cross-linker; Protein interactions; hmotnostní spektrometrie; Proteomics; reagencia zkříženě vázaná; New MS-cleavable cross-linker; Succinimides; Mass Spectrometry; zvířata; Urea; Humans